Analysis of reported cases of exogenous poisoning in the state of Piauí in the 2007 to 2017 (Research, Society and Development, 2020)
Poisoning accidents play an important role in the health field due to their high frequency, treatment costs and possibilities of irreversible sequelae. There was a high rate of exogenous intoxication, risks to the Piaui population and the need to conduct a study on. To characterize the compulsory reports of exogenous intoxication in the state of Piauí, outlining the main cities affected. This is an observational, retrospective, descriptive and qualitative study. The obtained data were pointed in statistical program Startistical Product Service Solucions( SPSS) – version 22.0. It was observed that Piauí has a growing number of reported exogenous intoxication cases. In 2007, the municipally with the highest prevalence of exogenous poisoning in the municipalities was Teresina , with 54.95% of cases, followed by Piripiri with 25.27%. Following the temporal analysis in 2017, the mark of 1586 cases of exogenous poisoning in Piauí were reported, with emphasis on the cities of Teresina, Floriano, Picos an Parnaíba, which together account for 83,32% of the total cases Notified. These data can be judiciously reduced through intervention planning and the development of policies and strategies to reduce these records. In the research area regarding self-medication poisoning data, it is understood that this problem can be avoided with the presence of the pharmacist who can develop a fundamental role in monitoring this public.